Identifying Needs and Barriers to Engage Family Members in Transplant Candidate Care. (June 2021) - McKinney, Warren T.; Bruin, Marilyn J.; Kurschner, Sophie; Partin, Melissa R.; Hart, Allyson
Introduction: Friends and family members provide critical support to patients on the waitlist for deceased donor kidney transplantation. However, little is known about how best to support and engage them effectively to improve patient outcomes. Methods: We conducted 5 focus groups with the family members of patients on the waitlist for a deceased donor kidney (n=23) to identify individual- and group-level targets for an intervention. Discussions encouraged participants to reflect on their support roles, experiences at the transplant evaluation, interactions with providers, knowledge of transplant options and expected outcomes. Transcripts of study sessions were coded using an iterative and inductive process. Results: The thematic analysis produced two main themes related to experiences providing care to patients on the waitlist for kidney transplantation. First, participants revealed that supporting a patient on the waitlist created challenges that reverberate through their entire social structure. Family members discussed frustrations with adapting to their patient's kidney health needs, feelings of isolation, and barriers to identifying and building effective support networks. Second, participants described multiple challenges that prevented their patient-family unit from making informed decisions about transplant care. These challenges included communication with their patient, patients resisting help, difficulty understanding the information, and feeling helpless. Conclusion: Family members providing care to patients with end-stage kidney disease require targeted support to overcome the unique challenges associated with their role in helping to meet their patient's clinical needs. Interventions to engage friends and family members in the care of kidney transplant candidates need to effectively address these challenges.